Cultural change in postwar Taiwan - Harrell, Stevan 1947- (Routledge, 2018)
Yet, despite the attention focused on the country's profound transformation, surprisingly little information exists on the concomitant changes that have occurred within the cultural matrix of arts and literature, religion and ritual, and the everyday life of Taiwan's people